Service Quality and Consumer Satisfaction at Fore Coffee: A Generation Z Study in Surabaya - Nesta, Giovani (Yayasan Kawanad, 2025)
The business world continues to evolve alongside rapid changes, particularly evident in the coffee shop sector's remarkable growth. This study aims to examine how service quality influences consumer satisfaction among Generation Z customers. The research population encompasses all Generation Z consumers in Surabaya, with a sample size of 100 respondents. Service quality serves as the independent variable, while consumer satisfaction functions as the dependent variable. Data collection utilized a questionnaire instrument, subsequently analyzed using SPSS version 26 software. Multiple linear regression was employed for data analysis. The findings demonstrate that service quality exerts a significant positive influence on Generation Z consumer satisfaction at Fore Coffee in Surabaya. The Adjusted R Square value of 64.6% provides empirical validation of these results.